Penile shaft involvement in pityriasis versicolor - Khaddar, Rym Kort (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
The Malassezia yeasts are among the normal human cutaneous flora in adults. They are also reported as part of the microflora of male genital region, mostly in uncircumcised males. The prevalence of Malassezia yeast colonizationon the glans penis of circumcised males is discussed in multiple studies. We report the case of a male patient with extensive pityriasis versicolor that does not involve the preputial space.
Keywords: Adult; dermatologija; glivične bolezni; kožne bolezni; Malassezia; Odrasli; Penis; Tinea Versicolor; Tinea verzikolor; Tunisia; Tunizija